Liderança de mercado na indústria automobilística Brasileira: O caso da Marcopolo - Luiz Ricardo Cavalcante; Bruno César Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The aim of this paper is to analyze the factors that explain the market leadership of a Brazilian bus bodywork manufacturer (Marcopolo). From a methodological point of view, the paper is a case study based on a bibliographic review and in-depth interviews.The underlying hypothesis is that some idiosyncratic factors regarding Brazilian market led the multinationals to give up contesting Brazilian incumbents in the bus bodywork segment. As compared to the automobile industry as whole, bus bodywork manufacturing is a relatively labor-intensive, smaller and less R&D-intensive industry, as innovation tends to be incremental. As a result, Brazilian companies managed to grow hand-in-hand with the local automotive market and dictated the customer-supplier relationship patterns. In order to become a relevant completely knocked down (CKD) vehicle exporter, Marcopolo had to develop technological capabilities related to stock management and lean production principles of modularity and product platforms or families. The firm relied basically on intramural research and development (R&D) and on vertical integration as a technology strategy to develop these capabilities. There seems not to be a relevant cooperative culture between Marcopolo and universities, research centers and other bus bodywork companies. However, there is cooperation between Marcopolo and companies outside the bus bodywork segment. Recently, Marcopolo found its own way to internationalization, especially towards developing countries, through acquisition of existing plants, joint-ventures and involvement of local suppliers. These movements, however, were not intended to be a source of new technologies. In short, Marcopolo's strategies and decisions have been ahead of the public policy rhetoric and of the market trends in Brazil. These strategies were clearly riskier, but, once succeeded, help to understand Marcopolo's leading position.
Keywords: L62; 330; Marcopolo; automobile industry; market leadership; bus bodywork manufacturing